Sociology of religion in America a history of a secular fascination with religion - Blasi, Anthony J. 1946- (Leiden Brill, 2014)
Sociology of Religion in America tells the story of the controversies involved in the development of a scientific specialty that often makes news in America. The evidence it presents runs contrary to the many myths about the field
Includes bibliographical references and indexes. Includes bibliographical references and index. - Print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Religion and sociology -- United States -- United States -- Verenigde Staten; Religion and sociology -- United States; POLITICAL SCIENCE ; Public Policy ; Cultural Policy; SOCIAL SCIENCE ; Anthropology ; Cultural; SOCIAL SCIENCE ; Popular Culture; Religion and sociology; Religionssoziologie; Godsdienstsociologie; Usa; United States; Verenigde Staten; Electronic books